An Alternative Outpatient Care Model: Postoperative Guest Suite–Based Care. (November 2014) - Hein, Rachel E.; Constantine, Ryan S.; Cortez, Robert; Miller, Travis; Anigian, Kendall; Lysikowski, Jerzy; Davis, Kathryn; Reed, Gary; Trussler, Andrew; Rohrich, Rod J.; Kenkel, Jeffrey M.
Background: Patients recovering from outpatient surgery are responsible for managing their pain, managing ambulation, and even implementing thromboembolism prophylaxis after discharge. Because of the importance of postoperative care to prevent complications, a model of care that helps a patient transition to independent self-care could provide optimal results. Objectives: The authors investigated the safety and morbidity rate for patients who underwent body contouring procedures and overnight care at an attached, nurse-staffed guest suite facility. Methods: A retrospective review was conducted of 246 patients who underwent major body contouring and who stayed at least 1 night in the guest suite facility. Major complications included a return to the operating room within 48 hours, major wound infection, and unplanned hospitalization within 48 hours. Minor complications included any postsurgical effect necessitating unplanned physician intervention within the first 30 days. Univariate analyses correlating patient characteristics and complication rates were conducted, as well as comparison of complication rates among same procedures reported in the literature. Results: The complication rate (major and minor complications) was 25.20%. Surgical site infection occurred in 8.13% of patients. The most common wound complication was erythema around the incision site (12.20%). Death, deep vein thrombosis, or pulmonary embolism did not occur. Comparison with relevant results reported in the literature indicated a significant reduction in the occurrence of postoperative venous thromboembolism. Conclusions: Patient education after surgery is essential to healing and adequate care. The guest suite model provides improved care and education for the patient and family postsurgery by addressing some of the known risk factors of plastic surgery. Level of Evidence: 4